2021
DOI: 10.1139/facets-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Fixing the Canadian Species at Risk Act: identifying major issues and recommendations for increasing accountability and efficiency

Abstract: Since the implementation of the Canadian Species at Risk Act (SARA) in 2003, deficiencies in SARA and its application have become clear. Legislative and policy inconsistencies among responsible federal agencies and the use of a subjective approach for prioritizing species protection lead to taxonomic biases in protection. Variations in legislation among provinces/territories and the reluctance of the federal government to take actions make SARA’s application often inefficient on nonfederally managed lands. Amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
14
0
4
Order By: Relevance
“…The status of salmon was instead based on two sources of informationexisting status designations under the Canadian Species at Risk Act (SARA) 2002 and field studies undertaken by the proponent. As no salmon species within the Skeena River watershed have been formerly assessed or listed under SARA (in fact, no commercially exploited species such as Pacific salmon have ever been listed under SARA; Schultz et al 2013;Turcotte et al 2021), the only information the EA drew upon to characterize the status of salmon was a 15-month field study conducted by the proponent to determine the presence of salmon in the study area. While this field study confirmed the presence of all species of salmon in the EA area, it did not consider any information on the status of the populations these salmon came from, despite the fact that information on salmon status and trends was readily available (Connors et al 2013).…”
Section: Ecological Fit: Temporalmentioning
confidence: 99%
“…The status of salmon was instead based on two sources of informationexisting status designations under the Canadian Species at Risk Act (SARA) 2002 and field studies undertaken by the proponent. As no salmon species within the Skeena River watershed have been formerly assessed or listed under SARA (in fact, no commercially exploited species such as Pacific salmon have ever been listed under SARA; Schultz et al 2013;Turcotte et al 2021), the only information the EA drew upon to characterize the status of salmon was a 15-month field study conducted by the proponent to determine the presence of salmon in the study area. While this field study confirmed the presence of all species of salmon in the EA area, it did not consider any information on the status of the populations these salmon came from, despite the fact that information on salmon status and trends was readily available (Connors et al 2013).…”
Section: Ecological Fit: Temporalmentioning
confidence: 99%
“…We first recorded habitat requirements from assessment reports and recovery documents (Table A1 in Appendix A). We used habitat requirements rather than "critical habitat" (SARA, 2002), due to ambiguity and biases in identifying critical habitat with limited data (Lemieux Lefebvre et al, 2018;Turcotte et al, 2021). We then paired the habitat requirements to land-cover classes from the Ontario Land Cover Compilation V.2.…”
Section: Identifying Habitats Of Species At Riskmentioning
confidence: 99%
“…A second major advance in our knowledge was the recent release of over 200,000 digitized fungal specimens from Agriculture and Agri-Food Canada's Canadian National Mycological Herbarium, Canada's largest collection of nonlichenized fungi, now searchable in Mycoportal.org. In the light of these major advances, as well as updates in the Canadian Species at Risk Act (Mooers et al 2010), the meaningful integration of Indigenous knowledge (Turner 2020;Turcotte et al 2021), and the recent interest in global fungal conservation, we present an update of the state of fungal conservation in Canada.…”
Section: Aspects Of Fungal Biology Challenging Classic Conservation A...mentioning
confidence: 99%